Transformation-defective mutant of avian myeloblastosis virus that is temperature sensitive for production of transforming protein p45v-myb. - Moscovici, M G (1985)
We have characterized a mutant of avian myeloblastosis virus (strain GA907/7) that shows a reduced capacity to transform myelomonocytic cells at the nonpermissive temperature. Myeloblasts transformed by this mutant suffer a substantial decrease in the amount of the transforming protein p45v-myb when shifted from the permissive to the nonpermissive temperature. We presume that the 5- to 10-fold decrease in the amount of p45v-myb causes the loss of the transformed phenotype. The decrease is due to a reduction in the level of v-myb mRNA. Mutant GA907/7 thus provides genetic evidence that p45v-myb is the transforming protein of avian myeloblastosis virus and apparently represents an unusual defect in the production or stability of mRNA.